EVALUASI PROGRAM PEMBINAAN DAN PENYULUHAN PERTANIAN DI UNIT PELAKSANA TEKNIS BANTU PENYULUHAN PERTANIAN (UPTB-PP) KAMPUNG KEMUNING MUDA KECAMATAN BUNGARAYA KABUPATEN SIAK TAHUN 2019 - Muhammad Aras; Rury Febrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The existence of the delegation of governmental authority to the regions in the era of autonomy and decentralization has a logical consequence in which the Regional Government is required to have adequate sources of funding, to assume responsibility for governance in ensuring regional independence and welfare. The implementation of regional governance is directed at efforts to empower the community (civil development) so that they are able to manage their resources according to local interests, priorities and potentials. So that the regions will be more advanced, independent, prosperous and competitive in the implementation of government and regional development. One of them is in the agricultural sector.               This study aims to describe the evaluation of agricultural guidance and counseling programs in Bungaraya District, Siak Regency in 2019 and describe the inhibiting factors for evaluating agricultural guidance and extension programs in Bungaraya District, Siak Regency in 2019. This data collection technique was carried out by interview and documentation. The method used in this research is descriptive qualitative.               The results showed that the success of the program implemented by UPTB PP Kampung Kemuning Muda, Bungaraya Subdistrict, Siak Regency in the form of counseling and coaching based on previously made objectives has benchmarks, where benchmarks are achieved properly by the resources managing them. With these benchmarks, it is necessary to evaluate the counseling and coaching carried out by the UPTB PP Kampung Kemuning Muda, Bungaraya District, Siak Regency. The success of the evaluation of the extension and guidance program policies carried out by UPTB PP Bungaraya Subdistrict together with related agencies, still encounters several obstacles, these internal and external obstacles come from the farmers / farmer groups themselves. The inhibiting factors for the evaluation of agricultural guidance and counseling programs in Bungaraya District, Siak Regency consist of external factors and internal factors. Internal factors in the limitations of the inadequate agricultural guidance and extension program (number and capacity) then external factors related to the importance of the availability of facilities and infrastructure for the Agricultural Development and Extension Program in the prevailing laws and regulations. Keywords: Evaluation, Development and Agricultural Extension